Vascular smooth muscle cell peroxisome proliferator-activated receptor γ protects against endothelin-1-induced oxidative stress and inflammation. Issue 7 (July 2017) - Idris-Khodja, Noureddine; Ouerd, Sofiane; Trindade, Michelle; Gornitsky, Jordan; Rehman, Asia; Barhoumi, Tlili; Offermanns, Stefan; Gonzalez, Frank J.; Neves, Mario F.; Paradis, Pierre; Schiffrin, Ernesto L.
Abstract : Aims: Peroxisome proliferator-activated receptor γ (PPARγ) agonists reduce blood pressure and vascular injury in hypertensive rodents. Pparγ inactivation in vascular smooth muscle cells (VSMC) enhances vascular injury. Transgenic mice overexpressing endothelin (ET)-1 selectively in the endothelium (eET-1) exhibit endothelial dysfunction, increased oxidative stress and inflammation. We hypothesized that inactivation of the Pparγ gene in VSMC (sm Pparγ −/− ) would exaggerate ET-1-induced vascular injury. Methods and results: eET-1, sm Pparγ −/− and eET-1/sm Pparγ −/− mice were treated with tamoxifen for 5 days and studied 4 weeks later. SBP was higher in eET-1 and unaffected by sm Pparγ inactivation. Mesenteric artery vasodilatory responses to acetylcholine were impaired only in sm Pparγ −/− . N ω -Nitro-L-arginine methyl ester abrogated relaxation responses, and the Ednra / Ednrb mRNA ratio was decreased in eET-1/sm Pparγ − / −, which could indicate that nitric oxide production was enhanced by ET-1 stimulation of endothelin type B receptors. Mesenteric artery media/lumen was greater only in eET-1/sm Pparγ − / − . Mesenteric artery reactive oxygen species increased in sm Pparγ − / − and were further enhanced in eET-1/sm Pparγ − / − . Perivascular fat monocyte/macrophage infiltration was higher in eET-1 and sm Pparγ − / − and increased further in eET-1/sm Pparγ − / − . Spleen CD11b + cells were increased in sm Pparγ − / − and further enhanced in eET-1/sm Pparγ − / −, whereas Ly-6C hi monocytes increased in eET-1 and sm Pparγ − / − but not in eET-1/sm Pparγ − / − . Spleen T regulatory lymphocytes increased in sm Pparγ − / − and decreased in eET-1, and decreased further in eET-1/sm Pparγ − / − . Conclusion: VSMC Pparγ inactivation exaggerates ET-1-induced vascular injury, supporting a protective role for PPARγ in hypertension through modulation of pro-oxidant and proinflammatory pathways. Paradoxically, ET-1 overexpression preserved endothelial function in sm Pparγ −/− mice, presumably by enhancing nitric oxide through stimulation of endothelin type B receptors. Abstract : Supplemental Digital Content is available in the text